School Environment and School Injuries - Salminen, Simo; Kurenniemi, Marja; Råback, Mirka; Markkula, Jaana; Lounamaa, Anne (Frontiers in Public Health, 2014)
Background: Although injuries at school are an important issue in public health, environmental factors in schools and school yards have seldom been the focus of school injury research. The goal of our investigation was to examine the effect of environmental factors on school injuries. Methods: Nine comprehensive Finnish schools registered school injuries over a period of two school years. Injuries were classified as being associated with environmental factors, suspected environmental factors, and others. The consensus between two independent classifiers was 81%. Results: A total of 722 injuries were classified. In 11.6% of these injuries, the physical environment factor was evident, and in 28.1% of the injuries, physical environment was suspected of being a contributory risk factor. Thus the physical environment of the school was a contributing factor in over a third (39.7%) of injuries occurring in the school, on the school yard or during the journey to or from school. In this study, conducted in Finland, ice on the ground was mentioned most frequently as an environmental risk factor. Conclusions: In Finland, the Nordic weather conditions are not taken into account in the school yard and playground plans as they ought to from the safety point of view. An initiative has been launched on a mandatory wintertime master plan for every school yard.